"Do they understand"? A case study of atypical institutional encounters. (September 2022) - Klemmensen, Charlotte Marie Bisgaard
Abstract: Individuals with impairments face challenges in their seeking to accomplish communicational goals. Despite continuous efforts to communicate, often they appear disregarded. A critical discussion of mutual understanding provides a basis for an investigation of institutional encounters. Video ethnography and field work were carried out in a residential care facility involving an individual with acquired brain injury and professionals. In revisiting the concept of 'communicational understanding', an analysis of the individual's efforts to communicate and the professionals' apparent disregard showed discrepancies. This research focused on a perceived lack of 'communicational care' in turning the spotlight towards the individual and mutual understanding. Highlights: Ethnographic observations of institutional encounters foreground the individual with acquired brain injury The professionals' response management presuppose the existence of mutual understanding Mutual understanding as concept is discrepant to a manifest lack of awareness of the individual's needs The professionals' choice of action interprets as an institutionalized lack of 'communicational care' refuting mutuality in understanding A critical approach to mutual understanding underpins the individual's perspective